Modification of Papaya Ringspot Virus HC-Pro to Generate Effective Attenuated Mutants for Overcoming the Problem of Strain-Specific Cross Protection - Cheng, Hao-Wen (Plant disease, 2023)
Cross protection application of HA5-1, an attenuated mutant of papaya ringspot virus (PRSV) HA strain from Hawaii, was withdrawn from Taiwan due to the narrow geographic strain specificity of HA5-1. Here, to overcome this problem, we created attenuated mutants of PRSV YK, a dominant severe strain from Taiwan, by mutating helper component protease (HC-Pro) at F7, R181, F206, and D397 residues critical for potyviral pathogenicity. PRSV YK HC-Pro R181I, F206L, and D397N single-mutant viruses induced mild symptoms, but their adverse effects on growth of papaya plants disqualified them as useful protective viruses. However, F7I single-mutant and F7I + F206L double-mutant viruses displayed mild symptoms followed by recovery, and they showed a zigzag pattern of accumulation in papaya plants, indicating their potential to trigger RNA silencing and retain partial antagonistic suppression of host defense. Although F7I + R181I and F7I + D397N double-mutant viruses caused symptomless infection, they accumulated barely above mock level and, thus, were not qualified as proper protective viruses. RNA silencing suppression (RSS) analysis by agroinfiltration in Nicotiana benthamiana plants revealed that the HC-Pro F7I and F7I + F206L mutant proteins were weaker in RSS ability than the wild-type protein. Under greenhouse conditions, F7I and F7I + F206L mutant viruses were genetically stable but not aphid transmissible. Compared with the HA5-1 mutant's low degree (10%) of protection to papaya plants, the F7I and F7I + F206L mutants provided complete (100%) protection to papaya and horn melon plants against strain YK. Thus, F7I and F7I + F206L mutants solve the problem of strain-specific protection and have great potential for control of PRSV in Taiwan